THE REALIZATION OF METAPHOR OF MODALITY USED IN DONALD TRUMP’S SPEECH IN UNITED NATIONS GENERAL ASSEMBLY 2017 - Nursyah Handayani; Siti Aisyah Ginting; Zanuddin Zainuddin (LINGUISTIK TERAPAN, 2019)
This Study investigates modality used by Donald Trump in his   speech  in  United Nations General Assembly 2017. Modality is expressed as the speakers’s judgment of the Obligation, or probabilities involved what is saying. The speech was conveyed by Donal Trump as the  representative of America in United Nations General Assembly 2017. Three objectives of the study are the describtion of  kinds of the modality used on  Donald Trump’s speech in United Nations General Assembly, the analyze of realization of modality and the describtion of the reasons of modality.the data were obtained from Donal Trump’s speech . The speech transcription was analyzed by applying Systemic Functional Linguistics Theory. The Occurences of modality were qualitatively analyzed by converting them into persentages to determine the proportions namely (i) explicitly subjective, (ii) imlicity subjective, (iii) explicitly objective and (iv) imlicity objective. The findings indicates that imlicity subjective (68.75 %) , ) explicitly subjective (17.19%), imlicity objective (7.81%) and explicitly objective (6.25%). It means that the speech is also conveyed methaphorically or congruently by grammatical variation which occurs is based on the logical semantic relationship projection and exert the pragmatic function to connct the listener perception toward the speaker judgmentKeywords: modality, explicitly subjective, imlicity subjective, explicitly objective, imlicity objective